Circulating endothelial-cell kinetics and viability predict survival in breast cancer patients receiving metronomic chemotherapy - Mancuso, Patrizia (The American Society of Hematology, 2006)
Antiangiogenic agents and therapeutic strategies have entered the clinical oncology arena. The classical tumor size measurements defined to monitor efficacy of chemotherapy, however, might not be appropriate for these newer therapeutics. We previously found that circulating endothelial cells (CECs) were increased in number and more viable in cancer patients compared with control subjects. We investigated the correlation between CEC kinetics and clinical outcome in patients with advanced breast cancer receiving metronomic chemotherapy, a therapeutic strategy associated with antiangiogenic activity and anticancer efficacy. CEC number and viability were measured by flow cytometry in patients and in preclinical models. CECs were decreased in patients for whom no overall clinical benefit (defined as a clinical response or a stable disease) was observed compared with those who had a clinical benefit (P = .015). This difference was due to an increased fraction of apoptotic CECs in patients with a clinical benefit. Univariate and multivariate analyses indicated that CEC values greater than 11/μL were associated with a longer progression-free survival (P = .001) and an improved overall survival (P = .005). Preclinical models indicated that the source of apoptotic CECs was most likely the tumor vasculature. CEC kinetics and viability are very promising as predictors of clinical response in patients undergoing metronomic chemotherapy.